Real World Evaluation of Next-Day Molecular Respiratory Infectious Disease Testing on Healthcare Resource Utilization and Costs - French AJ; Fragala MS; Evans AS; Upadhyay P; Goldberg SE; Reddy J (ClinicoEconomics and Outcomes Research)
Andrea J French, Maren S Fragala, Azia S Evans, Pallavi Upadhyay, Steven E Goldberg, Jairus Reddy HealthTrackRx, Denton, TX, USACorrespondence: Maren S Fragala, HealthTrackRx, 1500 Interstate 35W, Denton, TX, 76207, USA, Email Maren.Fragala@HealthTrackrx.comPurpose: Advancements in pathogen identification by diagnostic testing may improve patient outcomes. This study evaluated healthcare utilization and costs following diagnostic testing for acute oropharyngeal and respiratory tract infections (RTIs).Patients and Methods: Healthcare utilization and costs were evaluated in patients with acute oropharyngeal infections (n=1,172,693), and RTIs (n=4,005,228) who received a syndromic panel-based PCR test with next-day results (HealthTrackRx, Denton, TX), or no test in the IQVIA PharMetrics® Plus adjudicated claims database.Results: Statistically significant differences were observed between patients who received the PCR test compared to those who received no test. The PCR test cohort had lower total healthcare costs (mean = $5,601±$29,170, median = $807) versus the no test cohort (mean = $7,460±$40,817, median = $1,163) (p = 0.0014) over 6 months, and fewer outpatient visits, other medical service visits, emergency room visits, and inpatient stays (p< 0.0001). Similarly, those who received the PCR test for oropharyngeal infection trended towards lower total healthcare costs (mean = $4,393±$13,524, median=$844) than those who received no test (mean = $5,503±$34,141, median = $956) (p=0.0525) and had fewer outpatient and other medical services (p< 0.0001).Conclusion: Next-day molecular testing for respiratory and oropharyngeal infection lowers healthcare utilization and costs, suggesting improved patient care through reduced need for healthcare resources.Keywords: PCR, NAAT, syndromic multiplex testing, respiratory virus, influenza viruses, respiratory tract infection, pharyngitis, diagnostics, healthcare utilization